ASESMEN KERUSAKAN MEKANIS SEPANJANG RANTAI PASOK TOMAT DI KABUPATEN MERAUKE - Sri Wahyuni; Jamaludin Jamaludin; Yus Witdarko (Faculty of Agriculture, Musamus University, 2020)
Improper post-harvest handling in the supply chain can cause mechanical damage. This damage happened by the post-harvest processing activities of each supply chain actor. The purpose of this study was to identify the level of losses due to mechanical damage to tomatoes along the supply chain. The method used in this research is the purposive sampling method to determine the pattern of the tomato supply chain and the Snowball sampling method to obtain the next actors. The results obtained in this study are that there are five supply chain patterns in Merauke Regency. The longest tomato supply chain pattern is found in the fourth supply chain pattern, and the shortest pattern is in the III supply chain pattern. Post-harvest handling starts from farmers, collectors, small traders, and consumers. Tomato losses occurred along the supply chain by 9.40%, with details at the farmer level of 2.30%, the collectors by 4.27%, and small traders by 2.83%.